Exposing Milk Adulteration in Iraq Markets: Menguak Pemalsuan Susu di Pasar Irak - Azhar Lateef Jebur; Karar Saleh Abed; Amir Hilal Muhammad; Hussein Neama Hussein; Sura mohammed fatlawi (Universitas Muhammadiyah Sidoarjo, 2024)
This study evaluated eighteen unflavored milk samples from local markets in Karbala, Diyala, Basra, Kirkuk, Wasit, and Babil, Iraq, to detect adulteration. Using total solids measurements, refractive index tests, and iodine starch tests, we aimed to assess milk quality. Except for sample No. 6, all samples tested negative for starch, indicating minimal thickening agent adulteration. However, samples 4, 5, 11, and 13 failed the refractive index test, suggesting water adulteration. These findings highlight the need for better monitoring and regulation to ensure milk purity and protect public health across different Iraqi regions. Highlights: Identified milk adulteration in six Iraqi governorates. Sample 6 tested positive for starch adulteration. Samples 4, 5, 11, 13 failed refractive index test. Keywords: milk adulteration, Iraqi markets, quality control, refractive index, starch test